O papel dos fundos soberanos na economia mundial - Caparica, Rodrigo Ferreira de Carvalho (2010)
This paper is a survey of the literature on Sovereign Wealth Funds, highlighting topics such as their origins, objectives, impacts of their investments, transparency and performance of this government instruments in the recent global financial crisis. It also examines the creation of the Brazilian¥s Sovereign Wealth Fund seeking to highlight their pros and cons. We emphasize the need to observe consistent surpluses in the Current Account to justify the creation of these instruments. The mere existence of substantial amounts of international reserves does not serve as a prerogative for its creation. The sustainability and volatility of the sources of foreign exchange should be examined. Still, we emphasize that the Sovereign Wealth Funds are government investment vehicles which relevance in the financial market does not justify the fears that can cause relevant imbalances, despite the criticism and questions about the lack of transparency in disclosing information about their investments.